PENGARUH PEMBIAYAAN BANK SYARIAH TERHADAP LABA DAN BIAYA OPERASIONAL PERIODE COVID-19: STUDI PADA BANK SYARIAH DI INDONESIA - Sitii Nur Indah Rofiqoh; Ririn Tri Ratnasari; Alimin Alimin; M. Ala’uddin; Thoyyib Mas’udi; Anik Rufaidah; Fatin Fadhilah Hasib (JPSDa: Jurnal Perbankan Syariah Darussalam, 2022)
This paper aims to validate a potential financing of sharia banking to profit and operational cost on Covid-19 era. The secondary monthly SPS data is used to support the double-simple linear regression analysis. The result of f-statistic and t-statistic analysis shows that the potential financing of sharia banking significantly influence to the profit only. It means that a risk-sharing regulatory framework in sharia banking may provide the inner adjustment which any mismatch regarding maturity, risk, value or linkage with the real economy is corrected systematically on covid-19 era. It offers policy implication for regulators, supervisors and sharia banking Standard Operating Procedure (SOP).